ALGUMAS MEDIDAS MORFOFISIOLÃ“GICAS EM SEIS CULTIVARES DE ð˜—ð˜¢ð˜¯ð˜ªð˜¤ð˜¶ð˜® ð˜®ð˜¢ð˜¹ð˜ªð˜®ð˜¶ð˜® Jacq. - AlcÃ¢ntara, V. de B.; Almeida, A. R. P. de; Ghisi, O. M. A. A. (REVISTA DE AGRICULTURA, 2020)
ALGUMAS MEDIDAS MORFOFISIOLÃ“GICAS EM SEIS CULTIVARES DE ð˜—ð˜¢ð˜¯ð˜ªð˜¤ð˜¶ð˜® ð˜®ð˜¢ð˜¹ð˜ªð˜®ð˜¶ð˜® Jacq.